(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Air quality has been degrading due to increase in vehicles and industrial activities. These industrial activities and vehicles cause most of the air pollutants as gases, but some are very tiny solid particles, such as dust, smoke. Most commonly detected air pollutants are Sulphur Dioxide (SO2), particulate matter, Hydrocarbons (HC), Lead, Carbon Dioxide (CO2) and Carbon Monoxide (CO), Nitrogen Oxides (NOx), and smog. These air pollutants affect both the indoor and outdoor air. The indoor air is more polluted, due to the release of the air borne chemicals while cooking and from furniture. The polluted air is unsafe for human health. So, the need of an indoor automatic air purifier arises. This paper presents a thorough study of different techniques and models developed to monitor the air quality and hereby control the air purifier system.